Geração coca-cola: escrita de si, memória e cultura jovem em Feliz Ano Velho, de Marcelo Rubens Paiva - Silva, João Batista Peixoto da (2012)
The objective of this study is to investigate the universe of Brazilian youth culture in the 80s, in particular, its projection around a genre of writings focused on the theme of youth living experience in the context of Brazil‟s political openness and democratization. To this end, we selected the book Happy old year, of Marcelo Rubens Paiva, published in the the early 1980s, more precisely in 1982, while projecting portrait of the experience of youth who experienced the dilemmas of the time, giving the individual experience of Marcelo, associated with the event of an accident that left him in a wheelchair, the status of the testimony of a Young inserted in to the effervescent world transformations that marked the historical setting of Brazil at the time, including his experience in political activism and his narrative of memory surrounding the disappearance of his father, a victim of the repression of the years of lead. It is through autobiographical writing that the dilemmas faced by Marcelo gain projection in relation to the historical universe in which it is inserted, linking individual memory and social memory.